Audit Persediaan pada Perusahaan Manufaktur: Risiko, Kendala, dan Pertimbangan Opini Auditor - Tsara Zahira (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This qualitative study aims to identify the risk areas and constraints faced by external auditors in auditing inventory accounts in manufacturing companies, as well as to analyze their effects on the consideration of the fairness of inventory balances and their implications for audit opinions. Data were obtained through in-depth interviews with external auditors. The findings indicate that the main risk areas lie in the assertions of existence, accuracy, valuation, and cut-off, which give rise to findings such as discrepancies between physical quantities and recorded data, quantity misstatements, potential valuation errors resulting from differences between recorded values and net realizable value (NRV), as well as cut-off period issues. The auditors emphasized substantive audit procedures, particularly physical inventory count and valuation testing through net realizable value (NRV) and test of pricing, in evaluating these risks. In addition, constraints such as non-integrated systems and limited access to documents affect audit effectiveness. These findings and constraints may affect the consideration of the fairness of inventory balances if they exceed materiality and result in insufficient audit evidence, thereby influencing the audit opinion.